Aldosterone-to-Renin Ratio as a Diagnostic and Prognostic Marker in Resistant Hypertension: Insights from a Retrospective Observational Study on Age, Hormonal Dysregulation, and Anthropometric Correlates - Dr. Arbind Kumar Choudhary; Afreen Munir; Jeevan Susan George; Dr Hemalatha Selvaraj; Dr Anamitra Hait; Dr. Dharmalingam Thirunavukkarasu (Asian Journal of Pharmaceutical Research and Development, 2024)
Resistant hypertension (RH) presents a significant clinical challenge, often requiring multi-faceted management strategies. This study aimed to evaluate the utility of the Aldosterone-to-Renin Ratio (ARR) as a diagnostic tool in identifying potential hormonal contributors to RH. Methods: We retrospectively analysed data from 852 patients diagnosed with RH at Nandha College of Pharmacy, Erode between December 2023 and March 2024. Patients met specific criteria for RH, including uncontrolled blood pressure despite treatment with three or more antihypertensive agents from different classes, including a diuretic. Exclusion criteria included secondary causes of hypertension. ARR was calculated by dividing serum aldosterone concentration by plasma renin activity, with a ratio ≥ 20 considered suggestive of primary aldosteronism. Results: A strong association between advancing age and RH was observed, with mean age progressively increasing from 25.67 years in the youngest age group to 76.12 years in the oldest. Approximately 59.15% of hypertensive patients had RH, with nearly half (46.63%) attributable to evident secondary causes. Notably, the remaining 53.37% lacked a clear secondary cause. Analysis of ARR revealed a statistically significant positive correlation with age, suggesting a potential link between aging and hormonal dysregulation within the renin-angiotensin-aldosterone system (RAAS). Patients with RH also exhibited higher body weights, BMI, and waist circumferences compared to those with controlled hypertension. Conclusion: This study suggests that ARR may be a valuable tool for identifying potential hormonal contributors to RH, particularly in older patients. The observed association between age, ARR, and RH highlights the need for age-tailored management strategies that incorporate hormonal assessment and address modifiable risk factors such as obesity. Further research is warranted to validate these findings and explore the clinical implications of ARR-guided management in RH.